Assessing students - Dewi, Gusti Putu Rustika; Santosa, Made Hery; Dewi, Ni Luh Putu Eka Sulistia; Nitiasih, Putu Kerti (Journal on English as a Foreign Language, 2023)
The massive implementation of online learning is seen as a great movement in EFL learning during pandemic COVID-19. However, it has complexities in its practices, especially in conducting online assessment. This descriptive qualitative study aimed at exploring online assessment strategies used to assess writing and the challenges encountered by the teachers during the assessment. The data were collected through an online open-ended questionnaire administration to 16 EFL teachers. Thematic data analysis method was applied in analyzing the data by identifying themes and sub-themes from the data obtained. The result indicated that several online assessment strategies were utilized by the EFL teachers to assess writing, namely writing report, writing genre text, writing short story, writing summary, and answering essay-based test. Those strategies were done through learning management system (LMS) in which the delivery and submission of the assessment were done online. Some prominent challenges encountered by EFL teachers in conducting online assessment to assess writing skills included academic integrity, time allocation, punctuality, Internet access, and guidance and feedback. It implies that the online assessment strategy chosen by the teachers to assess students